2021
DOI: 10.1111/jace.17618
|View full text |Cite
|
Sign up to set email alerts
|

Surface layer of Pt‐O‐Ce bonds on CeOx nanowire with high ORR activity converted by proton beam irradiation

Abstract: To develop the state‐of‐the‐art polymer membrane fuel cells. Both maximization of oxygen reduction reaction (ORR) activity on Pt cathode and minimization of Pt content in the cathode are required. For this challenge, the defect interface on oxide support was modified by proton beam irradiation method. Pt‐CeOx nanowire/C (Pt/C = 0.02) was fabricated using the proton beam irradiation method. Since the radical density generated by proton beam irradiation is two orders of magnitude greater than that of electron be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 28 publications
(61 reference statements)
0
6
0
Order By: Relevance
“…As mentioned in the Introduction, the authors successfully formed a Pt-nanocoated layer on the CeO x NWs using the proton irradiation method. Furthermore, our electrochemical measurements confirmed that the formation of Pt–O–Ce bonds together with fine Pt particles in this nanocoated layer enhances the ORR on the Pt/C cathode . However, it is impossible to prepare the cathode powder for MEA using a small amount of high-energy proton radiation emitted from the tip of a small glass capillary attached to the ion accelerator.…”
Section: Results and Discussion Sectionmentioning
confidence: 51%
See 4 more Smart Citations
“…As mentioned in the Introduction, the authors successfully formed a Pt-nanocoated layer on the CeO x NWs using the proton irradiation method. Furthermore, our electrochemical measurements confirmed that the formation of Pt–O–Ce bonds together with fine Pt particles in this nanocoated layer enhances the ORR on the Pt/C cathode . However, it is impossible to prepare the cathode powder for MEA using a small amount of high-energy proton radiation emitted from the tip of a small glass capillary attached to the ion accelerator.…”
Section: Results and Discussion Sectionmentioning
confidence: 51%
“…Furthermore, our electrochemical measurements confirmed that the formation of Pt–O–Ce bonds together with fine Pt particles in this nanocoated layer enhances the ORR on the Pt/C cathode. 57 However, it is impossible to prepare the cathode powder for MEA using a small amount of high-energy proton radiation emitted from the tip of a small glass capillary attached to the ion accelerator. Therefore, to obtain the necessary amount of cathode powder for fabrication of MEA, electron irradiation experiments were conducted by adding C 2 H 5 OH to a suspension consisting of K 2 PtCl 4 aqueous solution and CeO x NWs (C 2 H 5 OH/K 2 PtCl 4 molar ratio = 5), as in the case of proton irradiation experiments.…”
Section: Results and Discussion Sectionmentioning
confidence: 99%
See 3 more Smart Citations